Effect of Level of Sorghum and WPC-80 on Quality of Sorghum Incorporated Chhana Cake - Barot Amitkumar M.; Pinto Suneeta V.; Dharaiya, Chetan N; Patel Sunil M. (Archives of Current Research International, 2024)
The objective of the present investigation was to develop a technology for manufacture of a millet based chhana cake. Sorghum incorporated chhana cake (SCC) was prepared using chhana as base material. Sorghum flour was added @ 20 % (w/w of chhana). Four batches of chhana were prepared from milk using different levels of milk fat, viz. 4.5, 5.0. 5.5 and 6.0%. It was found that chhana prepared from milk containing 6.0% milk fat was most suitable for preparation of SCC. The proportion of sorghum flour, blend of white butter and cottonseed oil (1.5:1.0 w/w) and WPC-80 in the formulation was optimized using Response Surface Method. The suggested solution was 25.31% sorghum flour, 25.52% blend of white butter and cottonseed oil (1.5:1.0 w/w) and 9.78% WPC-80 (w/w of chhana) and the desirability of the model was found to be 0.837. The Hardness (N), Cohesiveness, Springiness (mm), Guminess (N) and Chewiness (Nmm) of SCC was found to be 17.48, 0.26, 8.13, 4.28 and 35.02 respectively. The proximate composition of the developed product was: moisture 25.0 %, protein 13.8 %, fat 18.90 %, total carbohydrate 40.60 % and ash 1.68 %. The protein content of SCC was 14.5 % which was 2.9 times higher than commercial cakes.